THE CONCEPT OF LEGAL SUBJECT COMPETENCE IN THE AUTHORITY TO ACT ON MARRIAGE LAW IN INDONESIA - Martinelli, Imelda; Priyono, F.X. Joko; Yunanto, Yunanto (Indonesia Law Review, 2023)
This article focuses on discussing legal politics related to one important issue which is very basic, namely regarding the criteria for the ability to act of a human being as a legal subject within the scope of civil law, especially marriage law regarding the minimum age limit for entering into a marriage, who come from backgrounds with different interests and ideologies, make this an issue that can be highlighted. So the problem in this paper becomes whether there is a concept regarding the legal subject's competence in the authority to act on marriage law in Indonesia that accommodates the law in a unique manner? Problems will be answered using normative research methods that use secondary materials as well as legal and conceptual approaches. The conclusion is that there is still no unifying law regarding the authority to act on marriage law in Indonesia because the substance of marriage law is in an area that is not neutral and ambiguous because legal products are unificatory but the implementation of the law is sometimes still pluralistic.